A COMPARISON OF QUASI MONTE CARLO METHODS BASED ON FAURE AND SOBOL SEQUENCES FOR COMPUTATION OF MULTIDIMENSIONAL INTEGRALS: A COMPARISON OF QUASI MONTE CARLO METHODS BASED ON FAURE AND SOBOL SEQUENCES FOR COMPUTATION OF MULTIDIMENSIONAL INTEGRALS - Todorov, Venelin; Dzurov, Valeri; Dimitrov, Valentin (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
In this paper we implement and analyze the performance of Faure quasi-random sequence. We compare the results with the Sobol quasi-random sequence which is the most widely used quasi-Monte Carlo method. Also some experiments between Faure sequence and the plain (Crude) Monte Carlo method are given. We consider a case study with a non-smooth integrand function. We show that the Sobol sequence has some adv antageous over the Faure sequence.